Pengembangan Bahan Ajar Majalah Biopedia Tentang Keanekaragaman Belalang Pada Kawasan Hutan Kehati Sapen Nusantara Prigen Pada Kelas X MA Informatika Darul Ulum Candi Wates Prigen - Salsabila, Alfi Mirza (Jurnal Pendidikan Biologi Undiksha, 2023)
Research on the development of the biopedia magazine on biodiversity material, especially grasshoppers, is based on thisbecause there is still a lack of understanding of students in class X IPA MA Informatics Darul ulum Candi Wates Prigen andlearning resources in the form of biology LKS books are also still general and not specificWates Prigen and learning resourcesin the form of biology LKS books are also still general and not specific.This research and development aims to determine thefeasibility and preferences of the diversity of grasshopper class X IPA in MA Informatics Darul ulum Candi wates Prigen.This Biopedia magazine was developed using the Research and Development (R&D) research method using the 4D procedurewhich was developed by Melvyn I. in 1974. In this research it was limited to stage 3, namely develop (development), namelyproduct trials. The test subjects in this study were 1 material expert lecturer, 1 media expert lecturer, 1 biology teacher and 26students of class X IPA MA Informatics Darul ulum Candi wates Prigen. The instrument used was a feasibility and preferencevalidation questionnaire on the biopedia magazine.Based on the results of the material expert validation it was found that theproduct developed obtained very feasible criteria with a feasibility percentage of 87.77%, media experts obtained very feasiblecriteria with a feasibility percentage of 86.66%, the biology teacher's assessment obtained very practical eligibility criteriawith a practicality percentage of 91% and student response tests obtained a preference percentage of 83.88% so that biopdiamagazine about biodiversity, especially grasshoppers for class X IPA at MA Informatics Darul Ulum candi wates is veryfeasible and practical to use as a learning resource in learning activities.